Nilai Nasionalisme dan Religiusitas dalam Cerita Rakyat Ki Gede Sebayu - Selviana Nurhikmah; Bambang Sulanjari; Nuning Zaidah (EduInovasi: Journal of Basic Educational Studies, 2024)
The Ki Gede Sebayu folktale was one of the most renowned stories from Tegal and one of the founding figures of Tegal city. This study aimed to examine the depiction of nationalism and religiosity values in Ki Gede Sebayu folklore through three main aspects: infrastructure development, the role of religion, and community capacity building. A descriptive-qualitative approach was employed, with data collected through literature study and directed observation and analyzed using Levi-Strauss structuralism theory. The results indicate that the folklore of Ki Gede Sebayu reflected a number of values associated with nationalism, including love for the country, togetherness, mutual cooperation, courage, sacrifice, social justice, loyalty to the country, and exemplary leadership. Additionally, the value of religiosity is reflected through the spread of Islamic propagation as well as the construction of mosques and Islamic boarding schools. The conclusion of the Ki Gede Sebayu folklore was that it reflects the values of nationalism and religiosity. As a result, it was an important source of inspiration in the construction of the unity and pride of the Indonesian nation.